The effect of ischemic preconditioning on tennis exercise performance and the recovery subsequent to a simulated tennis match: A randomized controlled trial - Xin, Z.; Shi, Y.; Wu, Y. (International Journal of Sports Physiology and Performance, 2024)
Purpose The purpose of this study was to investigate the effects of acute ischemic preconditioning (IPC) on tennis skill and physical exercise performance, as well as to explore whether 7-day repeated IPC (RIPC) accelerated fatigue recovery after a simulated tennis match.